ACE2 Shedding and the Role in COVID-19 - Wang, Jieqiong; Zhao, Huiying; An, Youzhong (Frontiers in Cellular and Infection Microbiology, 2022)
Angiotensin converting enzyme 2 (ACE2), a transmembrane glycoprotein, is an important part of the renin-angiotensin system(RAS). In the COVID-19 epidemic, it was found to be the receptor of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). ACE2 maintains homeostasis by inhibiting the Ang II-AT1R axis and activating the Ang I (1-7)-MasR axis, protecting against lung, heart and kidney injury. In addition, ACE2 helps transport amino acids across the membrane. ACE2 sheds from the membrane, producing soluble ACE2 (sACE2). Previous studies have pointed out that sACE2 plays a role in the pathology of the disease, but the underlying mechanism is not yet clear. Recent studies have confirmed that sACE2 can also act as the receptor of SARS-COV-2, mediating viral entry into the cell and then spreading to the infective area. Elevated concentrations of sACE2 are more related to disease. Recombinant human ACE2, an exogenous soluble ACE2, can be used to supplement endogenous ACE2. It may represent a potent COVID-19 treatment in the future. However, the specific administration concentration needs to be further investigated.